Electronic documents in the Social Documents Section of the University Library in Toruń - Tondel, Roman (Folia Toruniensia, 2018)
Aim: The aim of the article is to present synthetic information about electronic documents in the collections of the Section for Social Life Documents of the University Library in Toruń (hereinafter: SSLD ULT). Research method: I used two methods: qualitative analysis and quantitative analysis of source materials. The first of these allows me to state that the SSLD of the ULT has, hitherto unknown, very interesting, cognitively important electronic documents for studies on various areas of social, cultural, scientific and political life in Toruń in the last few decades. The other method enabled. Conclusions: Among the electronic documents stored in the SSLD in the ULT, the most important place is occupied by documents that became part of the collections in accordance with the guidelines for gathering the Section’s collections, i.e. materials relating to the University, Toruń and Vilnius as well as evidence of the resistance movements’ activities in the times of People’s Polish Republic.